Modelling bioelectrochemical denitrification in absence of electron donors for groundwater treatment. (January 2022) - Taha, Ahmed; Patón, Mauricio; Ahmad, Farrukh; Rodríguez, Jorge
Abstract: Microbial electrochemical technologies (METs) have become a widely studied technology in recent years due to the need for sustainable biotechnologies. The scope of this work is the development of a mechanistic biokinetic model, based on first principles and a robust thermodynamic basis, to provide a theoretical accurate description of a MET system that would treat water contaminated with nitrate, the most common aquifer water pollutant, in absence of external electron donors. The model aims at describing the complex processes occurring including the competition between bioelectroactive and non-bioelectroactive reactions as well as the dynamics and kinetics of multiple bioelectrochemical reactions (both in series and in parallel) taking place in the same electrode. The bioelectrochemical denitrification of groundwater was then evaluated using the model as a case study. The evaluation focused on theoretical removal rates and energy expenditure, as well as the effect of key design parameters on the system's performance. The model successfully described how changes in the applied voltage and/or hydraulic retention time may impact the performance in terms of removal rate and effluent quality. The theoretical results also predict that the impact of electrode area is potentially more significant on the energy efficiency rather than on the effluent quality. Graphical abstract: Image 1 Highlights: MET-based denitrification is theoretically evaluated for a groundwater case study. An MET model for denitrification without electron donor is developed. Model mechanistically solves currents, potentials and intermediate concentrations. The model describes both parallel and serial bioelectrochemical reactions. The model connects design and operation with performance and efficiency.